2022
DOI: 10.3389/fimmu.2022.967371
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling reveals new serum signatures to discriminate lupus nephritis from systemic lupus erythematosus

Abstract: BackgroundLupus nephritis (LN) occurs in 50% of patients with systemic lupus erythematosus (SLE), causing considerable morbidity and even mortality. Previous studies had shown the potential of metabolic profiling in the diagnosis of SLE or LN. However, few metabonomics studies have attempted to distinguish SLE from LN based on metabolic changes. The current study was designed to find new candidate serum signatures that could differentiate LN from SLE patients using a non-targeted metabonomics method based on u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…This increase is characterized by elevated release of cytokines and chemokines, as well as increased infiltration of immune cells, predominantly myeloid cells. Additionally, we observed structural and metabolic damage in the glomerulus of patients with LN, observations consistent with previous studies and further validating our study’s convincing evidence ( 36 39 ).…”
Section: Resultssupporting
confidence: 93%
“…This increase is characterized by elevated release of cytokines and chemokines, as well as increased infiltration of immune cells, predominantly myeloid cells. Additionally, we observed structural and metabolic damage in the glomerulus of patients with LN, observations consistent with previous studies and further validating our study’s convincing evidence ( 36 39 ).…”
Section: Resultssupporting
confidence: 93%
“…All of these LN RG strains contain an anti-oxidant peroxiredoxin gene (PanPhlAn identifier xg001425), postulated to provide a competitive advantage in a host affected by oxidative stress from increased generation of reactive oxygen species (ROS) and reactive nitrogen species (RNS), which affects both host cells and gut commensals 14 15. Highly relevant, a recent metabolomics report found that increased serum ROS and RNS levels distinguish LN patients from non-renal SLE and healthy CTL 16. Further, both the S107-48 and S47-18 RG strains from LN donors contain orthologues of a putative RG PTS sugar transporter and for alpha-L-fucosidase (xg000037 and xg000038), which have been implicated in catabolism of host mucin that is a component of the intestinal barrier, although alone these factors are not currently considered sufficient to cause intestinal injury 17 18.…”
Section: Resultsmentioning
confidence: 99%
“… 14 15 Highly relevant, a recent metabolomics report found that increased serum ROS and RNS levels distinguish LN patients from non-renal SLE and healthy CTL. 16 Further, both the S107-48 and S47-18 RG strains from LN donors contain orthologues of a putative RG PTS sugar transporter and for alpha-L-fucosidase (xg000037 and xg000038), which have been implicated in catabolism of host mucin that is a component of the intestinal barrier, although alone these factors are not currently considered sufficient to cause intestinal injury. 17 18 Yet we found that the type strains, RG1 and RG2 also share 24 of the 34 above-mentioned IBD-associated genes ( figure 4 and online supplemental table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…In 11 studies, aromatic amino acids (tyrosine, tryptophan, and phenylalanine) were altered [ 44 , 45 , 49 , 51 , 53 , 57 , 79 , 80 , 105 , 110 , 111 ], four of which were found to be associated with SLE and PBC. Ten studies reported an alteration in branched amino acids (leucine, isoleucine and valine) [ 44 , 45 , 49 , 52 , 53 , 59 , 79 , 98 , 105 , 110 ], of which four studies found an association with SLE [ 49 , 52 , 53 , 59 ]. Alterations in fatty acids were observed in eight studies [ 44 , 50 , 53 , 57 , 61 , 104 , 106 , 108 ].…”
Section: Resultsmentioning
confidence: 99%